Scientific interpretations of discursive competence in teaching a foreign language to students of higher and secondary education - Anzhelika N. Kozlova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper presents a diachronic analysis of existing concepts of discursive competence and features of its formation among college students. Two stages of discursive competence (DC) studies are considered, including Western and domestic linguistic studies. The stages of development of the concept of discursive competence are traced based on the theory of communicative competence of D. Haims and N. Chomsky, which was then continued in the works of Canale and Swain and conceptualized for educational purposes by Celce-Murcia, Dornier and Turell. The component composition of the DC includes, according to Celce-Murcia, the categories of connectivity, integrity, conversational structures, compliance with the order in conversation. The Council of Europes Language Policy Regulation (CEFR) on the essence of discursive competence, which includes the students ability to arrange proposals in the desired sequence, was also considered. Russian linguists and teachers also contributed to the understanding of the recreation center, in particular, N.D. Arutyunova, L.O. Gelivera, A.G. Gorbunov, E.N. Elistratova, N.V. Popova and others. In a generalized form, according to their opinions, the formation of the recreation center includes the creation of coherent statements in compliance with their thematic organization, cohesion and coherence, the interaction of the author with the reader within the functional style required by the communication situation. The novelty of the presented research is to consider the methodology for forming a discursive competence in classes on a foreign language in college, using the authors textbook on discursive analysis. Experimentally, the author defines the main components of the formation of foreign-language discursive competence of college students and discloses their content for the implementation of oral and written communication of students.